2002
DOI: 10.1007/s15010-002-1121-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Extraintestinal Manifestations of Typhoid Fever

Abstract: Typhoid fever is a systemic disease caused by Salmonella typhi. Splenic abscess, subphrenic abscess and pancreatitis are rare complications of typhoid fever, with only one such case previously reported in the English literature [1][2][3][4].Here we report a patient with typhoid fever who developed splenic abscess, subphrenic abscess and pancreatitis.A 14-year-old Somalian boy presented with fever, chills, night sweats, abdominal pain and diarrhea for a period of 1 month. The physical examination was remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Other possible mechanisms linking typhoid fever and acute pancreatitis include toxin-induced and immunemediated pancreatitis. 34,35 The treatment and prognosis of myoglobinuric renal failure and acute pancreatitis associated with typhoid fever remain unclear. According to our review of reported cases, in addition to the current case, it seems to have a benign course.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mechanisms linking typhoid fever and acute pancreatitis include toxin-induced and immunemediated pancreatitis. 34,35 The treatment and prognosis of myoglobinuric renal failure and acute pancreatitis associated with typhoid fever remain unclear. According to our review of reported cases, in addition to the current case, it seems to have a benign course.…”
Section: Discussionmentioning
confidence: 99%
“…Toxin-induced and immune-mediated pancreatitis have also been postulated as other possible explanations. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Reports of focal infections like meningitis, abscesses, osteoarthritis and arterial infections caused by non-typhoid Salmonella have been published from the UK [49], where immunosuppression was the main risk factor [47]. Less frequently encountered complications of typhoid fever include splenic and sub-phrenic abscesses, pancreatitis, acute acalculus cholecystitis and wound infection [5052].…”
Section: Discussionmentioning
confidence: 99%